Min-Max Optimization of Emergency Service System by Exposing Constraints - Janacek, Jaroslav; Kvet, Marek (Communications - Scientific letters of the University of Zilina, 2015)
This paper deals with the fair public service system design using the weighted p-median problem formulation. Studied generalized system disutility follows the idea that the individual user’s disutility comes from more than one located service center and the contributions from relevant centers are weighted by some coefficients. To achieve fairness in such systems, various schemes may be applied. The strongest criterion consists in the process when the disutility of the worst situated users is minimized first, and then the disutility of better located users is optimized under the condition that the disutility of the worst situated users does not worsen. Hereby, we focus on the first step and try to find an effective solving method based on the radial formulation. The main goal of this study is to show how suitable solving method for the min-max optimal system design can save computational time and bring precise results.